Lung Cancer Occurrence—Correlation with Serum Chromium Levels and Genotypes - Piotr Baszuk; Beata Janasik; Sandra Pietrzak; Wojciech Marciniak; Edyta Reszka; Katarzyna Białkowska; Ewa Jabłońska; Magdalena Muszyńska; Monika Lesicka; Róża Derkacz; Tomasz Grodzki; Janusz Wójcik; et al. (Biological Trace Element Research, 2021)
Lung cancer is the leading cause of cancer-related death worldwide. Exposure to environmental and occupational carcinogens is an important cause of lung cancer. One of these substances is chromium, which is found ubiquitously across the planet. The International Agency for Research on Cancer has classified chromium(VI) as a human carcinogen. The aim of this study was to assess whether serum chromium levels, as well as DNA variants in selected genes involved in carcinogenesis, xenobiotic-metabolism, and oxidative stress could be helpful in the detection of lung cancer. We conducted a study using 218 lung cancer patients and 218 matched healthy controls. We measured serum chromium levels and genotyped ten genetic variants in ERCC2 , XRCC1 , MT1B , GSTP1 , ABCB1 , NQ01 , CRTC3 , GPX1 , SOD2 and CAT . The odds ratios of being diagnosed with lung cancer were calculated using conditional logistic regression with respect to serum chromium level and genotypes. The odds ratio for the occurrence of lung cancer increased with increasing serum chromium levels. The difference between the quartiles with the lowest vs. highest chromium level was more than fourfold in the entire group (OR 4.52, CI 2.17–9.42, p < 0.01). This correlation was significantly increased by more than twice when specific genotypes were taken into consideration ( ERCC –rs12181 TT, OR 12.34, CI 1.17–130.01, p = 0.04; CRTC3 –rs12915189 non GG, OR 9.73, CI 1.58–60.10, p = 0.01; GSTP1 –rs1695 non AA, OR 9.47, CI 2.06–43.49, p = < 0.01; CAT –rs1001179 non CC, OR 9.18, CI 1.64–51.24, p = 0.01). Total serum chromium levels > 0.1 μg/L were correlated with 73% (52/71) of lung cancers diagnosed with stage I disease. Our findings support the role of chromium and the influence of key proteins on lung cancer burden in the general population.